Impact of Tilt-Down Positioning Compared With Left Lateral Positioning on Ease of Colonoscope Insertion During Colonoscopy. Issue 6 (July 2020) - Early, Dayna; Larue, Sara; Weinstock, Leonard; Kushnir, Vladimir; Gyawali, Prakash; Sullivan, Shelby; Thyssen, Erik; Hollander, Thomas; Elsner, Jeffrey; Vyhmeister, Ross; Bhat, Trisha; Gaddam, Srinivas
Abstract : Goals: The aim of this study was to evaluate the efficacy of tilt-down (TD) versus left lateral (LL) positioning in speed and ease of colonoscope insertion in women with risk factors for difficult colonoscopy. Background: Risk factors for difficult colonoscopy in women include pelvic surgery, diverticulosis, and thin body habitus. Study: Female patients with body mass index (BMI) under 25, diverticulosis and history of pelvic surgery were randomized to TD or LL positioning. Five colonoscopists performed all studies at a single center. Time to splenic flexure and cecum, type and amount of medication administered, Boston Bowel Prep Score (BBPS), adverse events, and findings were recorded. The Mann-Whitney U test was used to evaluate the primary endpoint. Results: A total of 150 women were enrolled (81 TD, 69 LL). The mean age was 60.1 (SD 10.5) and the mean BMI was 23.9 (SD 3.5). In total 98 (65.3%) women had prior pelvic surgery, 94 (62.7%) had BMI <25 and 60 (40.0%) had diverticulosis. There was no statistically significant difference in time to the splenic flexure overall but insertion to the splenic flexure was significantly faster in the TD position as compared with the LL position in patients with diverticulosis (124 s for TD, 160 s for LL, P =0.022). In a linear regression analysis, lower BMI, diverticulosis and lower BBPS were significantly associated with a longer insertion time to the splenic flexure. There were no adverse events. Conclusion: TD positioning represents a straightforward maneuver to facilitate advancement through the sigmoid colon and may be beneficial in women with diverticular disease.